Dari Politeistik Menuju Kepada Monotesitik: Sejarah Perkembangan Keagamaan di Israel Kuna - Agus Santoso (RERUM: Journal of Biblical Practice, 2022)
The view of God's essence has been debated since the dawn of Christianity. This debate exposes whether Allah is polytheistic or monotheistic with its variants. In discussing this topic the authors use the method of the history of religion or Religionsgeschichte which is included in a series of critical historical methods. The result of this research is that God in Christianity is Monotheism here also not pluralism. Monotheism is meant here is monotheism which is more to individual responsibility. Monotheism is more to respect other individuals.   Pandangan tentang esensi Allah menjadi perdebatan sejak awal munculnya kekristenan. Perdebatan ini mengekspos apakah Allah itu politeistik atau monoteistik dengan variannya. Dalam membahas topik ini para penulis menggunakan metode sejarah agama atau Religionsgeschichte yang mana termasuk di dalam rangkaian metode historis kritis. Hasil dari penelitian ini adalah Allah dalam kekristenan adalah Monoteisme di sini juga bukanlah pluralisme. Monoteisme yang dimaksud di sini adalah monoteisme yang lebih kepada tanggungjawab individu. Monoteisme yang lebih kepada menghargai individu yang lain.